Avaliação do potencial microbiano do crescimento e de secreção de lacase do fungo amazônico lentinus crinitus (L.ex Fr.) F - Nepomucena, Rafaelle Maria Paz (2010)
This work was proposed to study the influence of four nutritional culture medium (açaí, cará, macaxeira and pupunha ) in the production of fungal biomass, laccase and secretion of the amazonic fungus Lentinus crinitus and to analyze the antimicrobial potential opposite bacterial strains pathogenic. L. crinitus presented greater production of biomass in medium supplemented with pupunha both under stationary and agitation conditions. About the activity of the ligninolytic enzyme laccase the maximum was obtained in the medium supplemented with cará (27,8 V.L-1) in the agitation condition. Abready in stationary condition, the medium supplemented with macaxeira presented the highest activity of this enzyme (15.16 V.L-1). In the presence of inductor veratryl alcohol (VA) L. crinitus had a significant in crease in the production of laccase both in stationary and agitation condition in all culture medium tested. Concerning the microbial potential, the waterish extract and alcoholic extract of L. crinitus body didn‟t present any bioassay or antimicrobial activity against the two strains S. aureus and E. coli. But the fungal metabolities of L. crinitus was verified the antimicrobial activity against the bacteria S. aureus and E. coli. Keyword : Fungal L. crinitus, Fungal biomass, Laccase , Antimicrobial.